Jamestown Canyon virus in Massachusetts: clinical case series and vector screening - Cormac M. Kinsella; Molly L. Paras; Sandra Smole; Samar Mehta; Vijay Ganesh; Lin H. Chen; Daniel P. McQuillen; Ruta Shah; Justin Chan; Matthew Osborne; Scott Hennigan; Frederic Halpern-Smith; et al. (Emerging Microbes and Infections)
Jamestown Canyon virus (JCV) is a neuroinvasive arbovirus that is found throughout North America and increasingly recognized as a public health concern. From 2004 to 2012, an average of 1.7 confirmed cases were reported annually in the United States, whereas from 2013 to 2018 this figure increased over seventeen-fold to 29.2 cases per year. The rising number of reported human infections highlights the need for better understanding of the clinical manifestations and epidemiology of JCV. Here, we describe nine patients diagnosed with neuroinvasive JCV infection in Massachusetts from 2013, the year of the first reported case in the state, to 2017. Because current diagnostic testing relies on serology, which is complicated by cross-reactivity with related orthobunyaviruses and can be negative in immunosuppressed patients, we developed and evaluated an RT-qPCR assay for detection of JCV RNA. We tested this on the available archived serum from two patients, but did not detect viral RNA. JCV is transmitted by multiple mosquito species and its primary vector in Massachusetts is unknown, so we additionally applied the RT-qPCR assay and confirmatory RNA sequencing to assess JCV prevalence in a vector candidate, Ochlerotatus canadensis. We identified JCV in 0.6% of mosquito pools, a similar prevalence to neighboring Connecticut. We assembled the first Massachusetts JCV genome directly from a mosquito sample, finding high identity to JCV isolates collected over a 60-year period. Further studies are needed to reconcile the low vector prevalence and low rate of viral evolutionary change with the increasing number of reported cases.